Epidural spinal angiolipoma: a case series - Wang, Fei Fei (BMC Res Notes, 2017)
BACKGROUND: Spinal angiolipomas (SAL) are rare benign tumors, commonly presenting with slow progressive spinal cord compression. There are only about 170 cases identified so far. Magnetic resonance imaging (MRI) has become the modality of choice for SAL. The purpose of this article is to report three cases of SAL and their characteristic MRI features. CASE PRESENTATION: Three cases of epidual spinal angiolipoma from ethnic Han Chinese patients are presented here, including one lumbar and two thoracic tumors. MRI imaging findings were reviewed. CONCLUSIONS: Multiple MRI technology for characterization of SAL provides useful information for differential diagnosis and therapeutic management.